RELEVANSI NILAI PENGUNGKAPAN INFORMASI RISIKO KEUANGAN PADA INSTRUMEN KEUANGAN DI ERA PANDEMI COVID 19 - Ramdani, Rahmat Fajar; Sisdianto, Ersi (ITB AAS Indonesia Surakarta, 2024)
The occurrence of the COVID-19 pandemic led to a decline in economic performance both on a micro and macro level, resulting in a higher risk of embedded financial instruments. Therefore, it became necessary to disclose information regarding financial risks associated with financial instruments through financial statements. This study aims to prove that the disclosure of financial risk information in financial instruments is relevant to investors' decisions. The research uses 16 companies in the consumer financing sub-sector as study objects, analyzed using a value relevance model proven through multiple linear regression analysis. This study uses observational data from the COVID-19 period, specifically the years 2020, 2021, and 2022 as the observation period. To measure the disclosure of financial risk information, the study employs a disclosure index based on PSAK 107. The results have shown that the disclosure of financial risk information in financial instruments did not significantly affect the stock prices of companies in the consumer financing sub-sector during the COVID-19 period. Therefore, it can be concluded that the disclosure of financial risk information does not have value relevance for investors' decisions.